PENGELOLAAN DANA DESA BERDASARKAN PERATURAN MENTERI DALAM NEGERI NOMOR 113 TAHUN 2014 (STUDI KASUS PADA NAGORI KAHEAN KECAMATAN DOLOK BATU NANGGAR KABUPATEN SIMALUNGUN - Effendi, Helwin; Jubi, Jubi; Susanti, Elly; Silaen, Musa Fernando (SULTANIST: Jurnal Manajemen dan Keuangan, 2019)
The results of this research can be concluaded that: 1. Lack of community participation to participate in village fund management planning, this is due to the lack of motivation of the community to participate in the deliberations. Then there was a delay in submitting a draft village regulation that had been agreed to be evaluated. 2. In the implementation, administration, reporting and accountability of village fund management in accordance with PERMENDAGRI Number 113 of 2014, it shows that the principles of participation in management, orderly and disciplined principles, principles of transparency and accountability principles have been carried out properly.The suggestion from this research is that the village government should develop a participatory concept and foster a sense of community motivation by providing education seminars on managing village funds and leading to the implementation of village governance. Then the village government should pay more attention to the applicable regulations in managing village finances in order to realize Good Governance.